THE XBRL TECHNOLOGY AND MARKET EFFICIENCY IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Jayani, Erni; Winata, Jumiadi Abdi; Harahap, Khairunnisa (Universitas Negeri Medan, 2020)
The problem in this research is the need for fast and accurate information in the format of the presentation of financial statements resulting in the distribution of information, and data management can be problematic. Therefore, a format for financial reporting systems, namely Extensible Business Reporting Language (XBRL), was formed. The purpose of this study was to determine the effect of XBRL technology, stock prices, Return on Assets (ROA), and institutional ownership on market efficiency (information asymmetry and stock trading volume). The population and sample of this study are banking companies listed on the Indonesia Stock Exchange from 2015-2016. The sampling method using a purposive sampling method and obtained a sample of 42 companies. Data collection techniques are carried out by taking data from the Indonesia Stock Exchange website (www.idx.co.id) and the site http://finance.yahoo.com. Data were analyzed with multiple regression tests after being declared normal with the normality test and though using SPSS 20. The results of this study simultaneously stated that XBRL technology, stock prices, ROA, and institutional ownership together have an influence on information asymmetry and stock trading volume. From the results of the study, it can be concluded that XBRL technology, stock prices, ROA, and institutional ownership cause a decrease in the level of information asymmetry and trading volume. This result also states that the company is in excellent condition when the value of information asymmetry decreases, but it is not good when the trading volume of its shares also decreases. Keywords: XBRL Technology; Stock Prices; Market Efficiency; Information Asymmetry; Stock Trading Volume.